EFFECTS OF SOME TREATMENT PROCESSESON MICROORGANISMSASSOCIATED WITH FRESH CARROTS FROM SELECTED MARKETS IN GOMBE METROPOLIS - Salawudeen, A.; Umar, A. T.; Suleiman, M.A; Wasa, Alibe A.; Yabilsu, B. M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
This study was aimed at analyzing the treatment effects of vinegar, salt and blanching on the growth of pathogenic microbes associated with fresh carrots. A total of 36 samples were bought from three different sellers in three different markets namely Gombe main market, Cross market and Tumfure market and then treated in the laboratory. The samples were subjected to the treatment processes for a precise contact time, the samples were further plated and isolates were observed for further result analysis. The mean colony count of the isolates obtained after treatment processes ranged from 1.34x102-1.85x102 with average counts of 1.55 X102 for vinegar, 1.98x103-2.32x103 with average counts of 2.14X103 for salt broth, 2.72 x104- 3.48x104 with average counts of 3.14 X104 for blanching while the mean count of the carrot without pretreatment ranged from 5.65x105-6.95x105 with average counts of 6.03 X105 for bacteria. The occurrence of fungi isolates ranged from 0-2 growth for vinegar, 1-4 growth for blanching, 9 growth for salt broth while the control had a range of 4- 16 species occurrence. The results obtained from the treatment of carrot indicates that the higher inhibitive effect of microbial growth was found to be associated with vinegar at 1.55 X102 cfu/mL and a negligible fungi growth while the average effect was found when salt was used at 2.14X103 with the least fungi inhibition while blanching has the least inhibitive effect at 3.14 X104cfu/ml for bacteria and appreciable inhibition of fungi growth. It can be concluded that vinegar had the antibacterial and antifungal effectiveness on the samples treated and the inhibitory activity ranges depending on the constituents of the reagents. Vinegar used had the highest inhibitory effect and greater susceptibility of the microorganisms due to the presence of acetic acid in the vinegar which is lethal to the existence and growth of the microorganisms while salt as broth had the mild effect and minimal susceptibility on the microorganisms and finally blanching was least effective and the susceptibility of the microorganisms was abridged. Vinegar should be used by both consumers and sellers to ensure the reduction of microorganisms and provide healthy fruits that can be stored for a long time or eaten with less pathogens.